BRAF(V600E) Mutation is Associated with Decreased Disease-Free Survival in Papillary Thyroid Cancer - Fraser, S; Go, C; Aniss, A; Sidhu, S; Delbridge, L; Learoyd, D; Clifton-Bligh, R; Tacon, L; Tsang, V; Robinson, B; Gill, A J; Sywak, M (World journal of surgery, 2016)
The BRAF (V600E) mutation is a recognised molecular marker in papillary thyroid cancer (PTC), reported incidence from 30 to 80 %. BRAF(V600E) aberrantly activates the MAPK pathway, a central regulator of cell growth and proliferation. Previous studies have reported conflicting data regarding the impact of BRAF(V600E) on clinicopathological features of PTC. The study aims to determine whether BRAF(V600E) is useful as a prognostic biomarker in PTC. A cohort study of patients undergoing surgery for PTC was undertaken. The primary outcome measure was disease-free survival. Secondary outcome measures were tumour size, nodal positivity and radioactive iodine ablation rate. All cases were re-examined to confirm PTC. Immunohistochemistry for BRAF(V600E) was performed on tissue microarrays. A single endocrine pathologist, blinded to clinicopathological data, interpreted staining. 496 patients with PTC were included, and 309 (62 %) were BRAF(V600E) positive. Tumour size was similar for BRAF(V600E)-positive and -negative tumours (21.3 vs. 23.2 mm, p = 0.23). BRAF(V600E)-positive patients were significantly older at first operation (mean age 45 versus 49 years, p = 0.003). BRAF(V600E)-positive PTCs had a higher rate of disease recurrence (12.9 vs. 5.6 %, p = 0.004), lymph node metastasis (44 vs. 29.4 %, p = 0.004) and extra-thyroidal extension (44 vs. 22 %, p < 0.001). Five-year disease-free survival was 89.6 % for BRAF(V600E) positive and 96.3 % for negative tumours, p < 0.001. There was no difference between groups for vascular invasion or multifocality. The mean follow-up was 57 months for both groups. BRAF(V600E) in PTC predicts an increased risk of lymph node metastasis, extra-thyroidal extension and reduced disease-free survival. It is an additional useful prognostic biomarker.